Evaluation of antihyperglycemic and antihyperlipidemic potential of Nelumbo nucifera seeds in diabetic rats - Shahnaz,; Khan, Hidayatullah; Ali, Farman; Shah, Afzal; Kamran, Farhat; Jahan, Sarwat (Penerbit Universiti Kebangsaan Malaysia, 2016)
The present study was aimed at evaluating antihyperglycemic and antihyperlipidemic activity of nuciferin and norcoclaurine constituents of N. nucifera seeds, a well-known medicinal plant. The alloxan (100 mg/kg b.w) induced diabetic rats (200-250 g) were divided into seven groups (n = 6). Group I; normal control, Group II; diabetic control, Group III; standard, Group lV-VII were fed with methanolic crude extracts (100, 200 mg/kg), nuciferin and norcoclaurine (10 mg/kg b.w.), received for 15 days in dose dependent manner. The study included different parameters; examination of oral glucose, fasting blood glucose, serum lipid profile and checking for body weight changes. In oral glucose examination, within 60 and 80 min of treatment, extracts, nuciferin and norcoclaurine significantly reduced blood glucose (p<0.05) and restored body weight in diabetic rats. Alloxan- induced diabetic rats showed 30-50% reduction of blood glucose level (p<0.05) and recovered 5-20% body weight at day 15 after ingestion of crude extracts (100-200 mg/kg b.w.); and nuciferin and norcoclaurine (each at 10 mg/kg b.w.). It also recovered significantly elevated biochemical parameters such as triglycerides (TG), low density lipoprotein (LDL), high density lipoprotein (HDL), total cholesterol (TC), serum urea and creatinine. Our findings indicated that N. nucifera seeds possess significant antihyperglycemic and antihyperlipidemic activity in diabetic rats.